Is antibiotic prophylaxis mandatory in laparoscopic incisional hernia repair? Data from the herniamed registry. (October 2018) - Kirchhoff, Philipp; Hoffmann, Henry; Köckerling, Ferdinand; Adolf, Daniela; Bittner, Reinhard; Staerkle, Ralph F.
Abstract: Background: Several meta-analyses showed that laparoscopic incisional hernia repair is associated with lower surgical site infection (SSI) rates compared to open repair. However, the efficiency of antibiotic prophylaxis (AP) in laparoscopic incisional hernia repair alone is unknown and needs evaluation. Due to increasing antimicrobial resistance, a major global health care problem, AP needs to be critically evaluated. The aim of this study was to investigate the impact of AP on the rate of SSI and complication-related reoperations in patients undergoing laparoscopic incisional hernia repair. Materials and methods: Prospectively documented data from the Herniamed Hernia Registry from 2009 to 2017 were retrospectively analysed. Multivariable analyses were used to study the influence of AP as well as further patient and surgery-related risk factors on SSI and complication-related reoperation rates. This was verified in a sensitivity analysis using propensity-score matching. Results: In the analysed time period 13′513 patients undergoing elective laparoscopic incisional hernia repair were recorded, of which 14.4% (n = 1949) did not receive AP. The overall SSI rate showed no significant difference when directly comparing patients with (0.74%) and without AP (0.97%; p = 0.262). In the multivariable analysis the presence of patient related risk factors (p = 0.015) and defect size >10 cm (p = 0.035) significantly increased the rates of SSI and complication-related reoperations. The propensity-score matching analysis verified that SSI rates are not significantly different between the two groups (p = 0.265). Conclusions: In cases of laparoscopic incisional hernia repair in patients without risk factors and moderate hernia diameter (<10 cm), routine administration of AP in laparoscopic incisional hernia repair does not seem to be justified. Highlights: Surgical site infection rate showed no significant difference when comparing patients with and without antibiotic prophylaxis. In laparoscopic incisional hernia repair antibiotic prophylaxis is not mandatory in the absence of risk factors. The risk of surgical site infections increases if one or more risk factors are present. Larger defect size, recurrent hernia and the presence of risk factors increase the risk of complication-related reoperations.